Answer:
![(8^{(2)/(3) } )^(4) = 256](https://img.qammunity.org/2020/formulas/mathematics/middle-school/djqp3npje0vzwjg64yadsl7lhtf9rrz5db.png)
Explanation:
Given
![(8^{(2)/(3) } )^(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ulk6yixhza5g6u7xp4rl6gmralon6a17bw.png)
Required
Simplify
To simplify this, we apply law of indices but first we start by solving the expression in bracket.
8 =2 * 2 * 2
8 = 2³
So, we substitute 2³ for 8
becomes
![((2^(3))^{(2)/(3) } )^(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4zx1qx92bmtqdpa8huq4eodr6v3c1esqq1.png)
From law of indices
==>
![(a^(m))^{(n)/(m) } = a^(n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sdxl2cdl9e1xal8rd2k99w3funh676c979.png)
So,
![(2^(3))^{(2)/(3) } = 2^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ej6kp1wmf8ont5gqoc9vg3jj2z3gek7my2.png)
At this point we have
=
![(2^(2))^(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/waob2db1m9o364jjnslttglwe04vehd238.png)
Also, from law of indices
![(a^(m))^(n) = a^(m.n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uqn5nacdbu308sz9ncg2oynrmkbkjkpdtc.png)
So,
=
![(2^(2))^(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/waob2db1m9o364jjnslttglwe04vehd238.png)
![(2^(2))^(4) = 2^(2*4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dyny0lrh3su9vsdfnxrere99plq15li1on.png)
![(2^(2))^(4) = 2^(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i8wgmqmzdd92vszatr30vzb4wmls3j941j.png)
![(2^(2))^(4) = 256](https://img.qammunity.org/2020/formulas/mathematics/middle-school/20cx0x89evthx20d1dart553l5frkl1e7s.png)
Hence,
![(8^{(2)/(3) } )^(4) = 256](https://img.qammunity.org/2020/formulas/mathematics/middle-school/djqp3npje0vzwjg64yadsl7lhtf9rrz5db.png)